Design and Simulation of 10 kHz Voltage-Source Three-phase Resonant DC-Link Inverter for 10 kW Ohmic Heating Process - Mohamed Ali, Elsadig (2001)
There has been much interest recently in heat processing and packing for rapid heating and non-thermal microbial inactivation of food. Ohmic heating is one of the new technologies used. It is an operation in which heat is internally generated within foods due to the passage of alternating electrical current. Much of the research carried out on ohmic heating to date has been done using frequency of 60 and 50 Hz. Low frequency has an electrolytic effect similar, though to a lesser extent to that of direct current. The major electrolytic effect is the dissolution of the metallic electrodes, which may contaminate the product. One of the most effective methods utilised to overcome the electrolytic effect, and give high performance of ohmic heating is high frequency resonant converter. The literature review includes resonant DC-link inverter, three-phase sinusoidal PWM inverter, control of the inverter, filters design, ohmic heating, and power MOSFET. Sinusoidal pulse width modulation was used to produce pure sinusoidal current at high frequency and low harmonics. Although it had drawbacks such as suffering high stress and losses during switching these effects were reduced by soft switching, where the MOSFET is switched on at zero voltage (ZVS). Power MOSFET was chosen for high switching device, low resistance and feature suitable for static power converter. The study presented the design for 10 kHz of voltage-source resonant DC-link inverter involving the design of three-phase rectifier, filter, resonant circuit, sinusoidal PWM inverter and control circuit. The performance of three-phase resonant dc-link inverter was simulated based on the design parameters. Three-phase sinusoidal output current at 10 kHz was produced, which is suitable for driving AC resistive load (ohmic heating).